Risk Factors for Adolescent Pregnancy in Bali: Case Control Study - Dewi Aprelia Meriyani; Desak Putu Yuli Kurniati; Pande Putu Januraga (Universitas Udayana, 2016)
Background and purpose: Adolescents pregnancy is a public health problem in Indonesia. The 2012 Demographic and Health Survey Indonesia showed that 9.5% women aged 15-19 years had given birth. The aim of this study was to identify risk factors associated with adolescent pregnancy. Methods: The study was conducted in Kintamani District, Bangli, Bali Province. Design of the study was case control with a total of 96 respondents. The cases were 32 pregnant woman age <20 years and the controls were 64 non married and non pregnant woman age <20 years. The cases were taken from register of pregnant women in Kintamani I and VI primary health care centers. The controls were randomly taken from a list of women in the youth group at the same working area of both primary health care centers. The data collection was conducted by interview in the house of each respondent. The data were analyzed using bivariate (chi square test) and multivariate logistic regression. Results: Risk factors that found associated with adolescents pregnancy were respondents with peer negative influence (AOR=71.6; 95%CI: 9.4-545.2), respondents who had opportunity to have sexual relationship (AOR=17.7: 95%CI: 3.2-98.2), lack of knowledge about reproductive health and adolescent pregnancy (AOR=12.8; 95%CI: 2.5-66.5) and higher family income (AOR=5.8: 95%CI: 1.3-26.6). Level of education and exposure to pornography was not significantly found associated with adolescent pregnancy. Conclusion: The negative influence from their peers, opportunity to have sexual intercourse, lack of knowledge and higher family income were found as risk factors of adolescents pregnancy.